2005
DOI: 10.1002/smj.503
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency, flexibility, or both? Evidence linking strategy to performance in small firms

Abstract: This paper analyzes small firm performance in relation to efficiency and flexibility strategies. Using configuration theory, the authors propose that small firms that pursue efficiency strategies or flexibility strategies outperform those that attempt to pursue both. Additionally, size is used as a configurational attribute to develop competing hypotheses on whether efficiency strategies or flexibility strategies are better suited for small firm performance. In two samples of 200 and 144 privately-held small f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
304
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(324 citation statements)
references
References 48 publications
14
304
3
3
Order By: Relevance
“…Thus, the finding departs from certain findings in earlier research that stress the difficulties that small firms may face in combining competing strategies (cf. Ebben & Johnson, 2005;Hughes et al, 2007). On the other hand, the finding may also reflect the fact that business model innovation activities and replication activities may partly overlap, particularly in small firms: an initial 'proto' business-model may be further developed in the course of its replication efforts (Chesbrough & Rosenbloom, 2002;Winter & Szulanski, 2001).…”
Section: Contributions To Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the finding departs from certain findings in earlier research that stress the difficulties that small firms may face in combining competing strategies (cf. Ebben & Johnson, 2005;Hughes et al, 2007). On the other hand, the finding may also reflect the fact that business model innovation activities and replication activities may partly overlap, particularly in small firms: an initial 'proto' business-model may be further developed in the course of its replication efforts (Chesbrough & Rosenbloom, 2002;Winter & Szulanski, 2001).…”
Section: Contributions To Researchmentioning
confidence: 99%
“…On one hand, small firms' often-cited characteristics are their limited resources and relatively modest ability to shape their environment (e.g. Cooper, Gimeno-Gascon, & Woo, 1994;Ebben & Johnson, 2005;Gibb, 2000;Lee, Lim, & Tan, 1999). Therefore, the strategic choice to innovate novel business models (as opposed to imitate ones existing in the market) might lead, on average, to inferior financial performance for small firms.…”
Section: Financial Performance Implications Of the Strategic Emphasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement in efficiency is usually a loss in flexibility. The authors identify many cases, including agriculture (that provides several examples of this phenomenon), in which flexibility is achieved at the expense of a loss of efficiency, an issue that Adler et al, 1999, Ebben andJohnson, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Although strategic purity initially received considerable support, (Dess & Davis, 1984;Hawes & Crittendon, 1984;Roos,Flinkman, Jä ppinen, Lönner & Warensjö, 2002;Lä htinen & Toppinen, 2008), it was challenged in later studies (Campbell-Hunt, 2000;Parnell & Hershey, 2005;Raynor, 2007;Salavou, 2010;Huang, 2011;Salavou, 2013;Shinkle, Kriauciunas & Hundley, 2013). While some studies revealed that pure strategies improved performance (Ebben & Johnson, 2005;Lechner, Gudmundsson & Vidar, 2014;Hansen, Nybakk & Panwar, 2015), others suggested that different generic strategies were linked to different aspects of performance (Chandler & Hanks, 1994;Baum, Locke & Smith, 2001). There is another group of studies, which indicated that hybrid strategies, combining elements of both generic competitive strategies, simultaneously lead to better performance (Carter, Stearns & Reynolds, 1994;Kim & Choi, 1994;Acquaah & Yasai-Ardekani, 2008; Pertusa-Ortega, Molina-Azorí n & Claver-Corté s, 2009; Leitner & Güldenberg, 2010;Hodgkinson, 2013;Parnell, 2013;Manev, Manolova, Harkins & Gyoshev, 2014;Salavou, 2015).…”
Section: Introductionmentioning
confidence: 99%